Shall We Talk about This? Reflections on Angela Jones’s Book ‘Camming: Money, Power, and Pleasure in the Sex Work Industry - Belyavskaya, Elena (Journal of Economic Sociology, 2024)
This review introduces economic sociologists to Camming: Money, Power, and Pleasure in the Sex Work Industry by Angela Jones, the first comprehensive study of the virtual market for sexual services. Jones’s book delves into the social impacts of the digital transformation within the sex industry, where online platforms create new employment opportunities for students, homemakers, individuals with health limitations, and other workers, often displaced from traditional labor markets. The review emphasizes three key aspects of Jones’s analysis that are particularly relevant for economic sociologists. The first is the normalization of sex work’s commercialization. The labor market crisis has rendered sex work a viable and socially inclusive form of employment, enabling participants to overcome alienation and find meaning in their work, where pleasure itself becomes a driving motivation. Jones’s work highlights the role of pleasure not only in the realm of sexuality but also as a factor in occupational and social spheres. The second focus is the transformation of norms and pathologies within sexuality, influenced by economic, social, and political dynamics. Jones argues that platform and emotional capitalism not only meet repressed physical and emotional needs but also actively shape new social expectations, reshaping the prevailing model of subjectivity in society. The third aspect is biopolitics and bodily autonomy. Digital platforms increasingly regulate intimate areas of life, extending their influence over personal autonomy and individual agency. The review underscores the provocative insights and empirical findings of Jones’s study, encouraging readers to engage with the book. Such engagement allows one to view the work not only as a distinctive contribution to contemporary American sociology but also as an opportunity to consider political, social, and cultural frameworks used to legitimize previously tabooed spheres through market forces.